An educational intervention maximizes children's learning during a zoo or aquarium visit. Issue 5 (2nd September 2020) - Collins, Courtney; Corkery, Ilse; McKeown, Sean; McSweeney, Lynda; Flannery, Kevin; Kennedy, Declan; O'Riordan, Ruth
Abstract: Children comprise many of the visitors to zoos every year, yet few studies have explored the impact of a zoo visit on children's learning. This study employed a repeated measure design using data gathered from 500 questionnaires to investigate students' knowledge, attitude, and behavior before and after visiting a zoo or aquarium in Ireland. A treatment group participated in a purposefully developed educational intervention, which included a hands-on activity, intended to enhance learning. Results indicate that learning does occur after a zoo or aquarium visit. However, students visiting the zoo and those who participated in the educational intervention showed the greatest increases in learning. A zoo visit has educational benefits for children, but to maximize this benefit an educational intervention should be offered.